Hype or hope: The role of alcohol septal ablation in improving outcomes for young patients with obstructive hypertrophic cardiomyopathy: A case series - Saputri, Vemmy Lian; Rizal, Ardian; Rahimah, Anna Fuji; Karolina, Wella; Yogibuana, Valerinna; Prasetya, Indra (Heart Science Journal, 2025)
Background: Hypertrophic cardiomyopathy (HCM) is a disease that has a poor prognosis and a higher likelihood of death in young people. Alcohol septal ablation (ASA) is a minimally invasive procedure that involves the injection of ethanol through a septal perforator to lead to infarction of the hypertrophied septum. This case series aims to present data on the beneficial effects of ASA in promoting hope for enhanced outcomes in young patients with HCM. Case: Patient 1: A 32-year-old male with HCM has been suffering from chest discomfort and atrial fibrillation since 2020. Echocardiography detected an increased obstruction in the left ventricular outflow tract (LVOT), resulting in a gradient of 104 mmHg. The patient underwent ASA to decrease the gradient to 37 mmHg, reducing hospitalizations throughout a 12-month follow-up period. Patient 2: A 27-year-old female diagnosed with HCM has been frequently suffering episodes of near syncope and shortness of breath with light activity over the past 6 months. The echocardiography findings showed a significant increase in the resting gradient in the LVOT. Following ASA, the resting gradient decreased to 54 mmHg during a 3-month follow-up. The patient did not suffer further near syncope events, and her NYHA functional class improved throughout a 9-month follow-up period. Conclusion: The effectiveness of ASA as a treatment option is hope for young patients with obstructive HCM, which is demonstrated in this case series, leading to relieving symptoms, reduced repeated hospitalization, and improved functional capacity.